2015
DOI: 10.4236/msa.2015.62021
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Supersaturated Solid Solutions Bi-Ag and Bi-Zn by Rapid Solidification Using Melt Spinning Technique

Abstract: Two eutectic alloys Bi-Ag and Bi-Zn were rapidly solidified using melt-spinning technique. X-ray diffraction analysis (XRD), differential scanning calorimetry (DSC), and temperature dependence of resistivity (TDR) were performed. The solid solubility of both Ag and Zn was extended to the eutectic concentration due to rapid solidification by melt spinning technique and both alloys are single-phase solid solutions. The addition of Ag extended the unit cell in both a and c directions keeping the axial ratio c/a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In addition, the structure of pure metals or alloys rapidly solidified from the melt is always unusual in some respect, even if the phases present have the same crystal structure as in the equilibrium pure metals or alloys. Recently, it was found that rapid solidification can produce semiconductors directly in some alloy systems [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the structure of pure metals or alloys rapidly solidified from the melt is always unusual in some respect, even if the phases present have the same crystal structure as in the equilibrium pure metals or alloys. Recently, it was found that rapid solidification can produce semiconductors directly in some alloy systems [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Other investigated alloys are from the Bi-Ag, Bi-Sb, Bi-Sn, Bi-Zn, or Bi-Sn-Zn systems, where further investigations are necessary for better understanding. The addition of Bi decreases the melting point of the system and improves the wettability, and up to a certain extent, the mechanical properties could also be improved [7,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The solute atoms play an important role in formation of semiconductors by rapid solidification. In this respect, a series of rapidly solidified Bi based semiconductor alloys were produced using melt spinning technique [2]- [4]. They found that the semiconducting behavior depended on the type of the solute atoms added to Bi.…”
Section: Introductionmentioning
confidence: 99%